RITUAL UJIAN NASIONAL: TRANSFORMASI PENGHORMATAN LELUHUR PADA KOMUNITAS KROWE DI KABUPATEN SIKKA - Utama, Bakti (Kebudayaan, 2016)
AbstractNational Examination in Indonesia is considered as a determinant for studentsâ??graduation. In recent years, several high schools in Sikka district held a ritual everytime before national exam. This paper discusses the ritual practices of the NationalExamination, especially at a high school in the mountains of Central Sikka. The purposeof this article is to answer whether national ritual practice exam is a new phenomena orrooted in the traditions of ancestors worshiping at Adat Community of Krowe in Sikka.For this purpose data have been collected through literature study, observation, andinterviews on Krowe people. Based on the collected data, the main argument of this paperis that the National Examination ritual practice is a form of transformation in ancestorworshipping ritual rooted in the Krowenese tradition. In this discussion, transformationrefers to the change in surface level but on a deeper level unchanged. Thus, although thenational exam ritual is an new expression of Krowenese belief, but at a deeper level is amanifestation of their tradition of ancestors worshiping.Â AbstrakUjian Nasional di Indonesia dianggap sebagai penentu kelulusan siswa, sehinggadilakukan berbagai usaha untuk menjamin kelulusan mereka. Pada beberapa tahunterakhir, beberapa sekolah menengah di Kabupaten Sikka mengadakan ritual setiapkali akan menghadapi ujian nasional. Tulisan ini membincangkan praktik ritual UjianNasional (UN), khususnya di sebuah sekolah menengah atas di pegunungan SikkaTengah. Tujuan tulisan ini adalah menjawab apakah praktik ritual ujian nasional tersebutmerupakan fenomena baru atau berakar pada tradisi penghormatan kepada leluhur padaKomunitas Krowe di Sikka. Untuk tujuan tersebut, data telah dikumpulkan baik melaluistudi literatur, observasi, maupun wawancara dengan Orang-orang Krowe. Berdasarkandata yang terkumpul tersebut, argumentasi utama tulisan ini adalah bahwa praktik ujiannasional merupakan bentuk transformasi ritual penghormatan leluhur yang telah berakarpada tradisi Komunitas Krowe. Dalam diskusi ini, transformasi merujuk pada terjadinyaperubahan pada tataran permukaan tetapi pada tataran yang lebih dalam tidak mengalamiperubahan. Dengan demikian, walaupun ritual ujian nasional merupakan ekspresi barukepercayaan orang Krowe, namun pada tataran yang lebih dalam merupakan wujud daritradisi mereka atas penghormatan kepada leluhur.